Iceberg calving dynamics of Jakobshavn Isbræ, Greenland - Amundson, Jason Michael (2010)
Thesis (Ph.D.) University of Alaska Fairbanks, 2010 Jakobshavn Isbræ, a fast-flowing outlet glacier in West Greenland, began a rapid retreat in the late 1990's. The glacier has since retreated over 15 km, thinned by tens of meters, and doubled its discharge into the ocean. The glacier's retreat and associated dynamic adjustment are driven by poorly-understood processes occurring at the glacier-ocean interface. These processes were investigated by synthesizing a suite of field data collected in 2007 2008, including timelapse imagery, seismic and audio recordings, iceberg and glacier motion surveys, and ocean wave measurements, with simple theoretical considerations. Observations indicate that the glacier's mass loss from calving occurs primarily in summer and is dominated by the semi-weekly calving of full-glacier-thickness icebergs, which can only occur when the terminus is at or near flotation. The calving icebergs produce long-lasting and far reaching ocean waves and seismic signals, including "glacial earthquakes". Due to changes in the glacier stress field associated with calving, the lower glacier instantaneously accelerates by ~3% but does not episodically slip, thus contradicting the originally proposed glacial earthquake mechanism. We furthermore showed that the predominance of calving during summer can be attributed to variations in the strength of the proglacial ice melange (dense pack of sea ice and icebergs). Sea ice growth in winter stiffens the melange and prevents calving; each summer the mélange weakens and calving resumes. Previously proposed calving models are unable to explain the terminus dynamics of Jakobshavn Isbræ (and many other calving glaciers). Using our field observations as a basis, we developed a general framework for iceberg calving models that can be applied to any calving margin. The framework is based on mass continuity, the assumption that calving rate and terminus velocity are not independent, and the simple idea that terminus thickness following a calving event is larger ...